2014
DOI: 10.7554/elife.02882
|View full text |Cite
|
Sign up to set email alerts
|

Three pools of plasma membrane cholesterol and their relation to cholesterol homeostasis

Abstract: When human fibroblasts take up plasma low density lipoprotein (LDL), its cholesterol is liberated in lysosomes and eventually reaches the endoplasmic reticulum (ER) where it inhibits cholesterol synthesis by blocking activation of SREBPs. This feedback protects against cholesterol overaccumulation in the plasma membrane (PM). But how does ER know whether PM is saturated with cholesterol? In this study, we define three pools of PM cholesterol: (1) a pool accessible to bind 125I-PFO*, a mutant form of bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
404
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(421 citation statements)
references
References 44 publications
15
404
1
1
Order By: Relevance
“…Despite an increased liver cholesterol level in either LDLRnull or Arh/Dab2 double-knockout mice, we observed that liver HMGCR expression was greatly induced, to a similar extent in both mutant mice. This is consistent with the finding that cellular cholesterol is compartmentalized, and only a certain pool of cholesterol is able to regulate HMGCR (32). Therefore, the endothelial cholesterol derived from LDL uptake likely is exchangeable with the hepatic pool of cholesterol that is capable in the feedback regulation of its de novo synthesis.…”
Section: Discussionsupporting
confidence: 89%
“…Despite an increased liver cholesterol level in either LDLRnull or Arh/Dab2 double-knockout mice, we observed that liver HMGCR expression was greatly induced, to a similar extent in both mutant mice. This is consistent with the finding that cellular cholesterol is compartmentalized, and only a certain pool of cholesterol is able to regulate HMGCR (32). Therefore, the endothelial cholesterol derived from LDL uptake likely is exchangeable with the hepatic pool of cholesterol that is capable in the feedback regulation of its de novo synthesis.…”
Section: Discussionsupporting
confidence: 89%
“…Ceramide is a sphingolipid the concentration of which is less than 1 mol% (compared to approximately 10 mol% sphingomyelin) in cellular membranes (9). It is mainly synthesized in the endoplasmic reticulum (ER) by ceramide synthases (CerSs), which attach a variety of fatty acid residues to long chain bases such as sphingosine and dihydrosphingosine, or by hydrolysis of sphingomyelin that is catalyzed by different sphingomyelinases (SMases) in distinct cellular compartments such as the plasma membrane, lysosomes, the Golgi apparatus, and mitochondria (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…These images demonstrate that accessible cholesterol, as judged by PFO* or ALO-D4 binding, is not evenly distributed over the entire plasma membrane but instead is highly enriched on microvilli. (1,2). They found that plasma membrane cholesterol is "accessible" to 125 I-PFO* binding when cholesterol levels are high (exceeding 35 mol% of all membrane lipids).…”
mentioning
confidence: 99%
“…Interventions that increased plasma membrane cholesterol levels resulted in more 125 I-PFO* binding (1). They went on to show that much of the cholesterol in the plasma membrane is sequestered by sphingomyelin and cannot bind 125 I-PFO* unless the sphingomyelin is destroyed with sphingomyelinase (SMase) (2). The studies by Das et al were very important because they characterized distinct pools of cholesterol in the plasma membrane (an accessible pool and a sphingomyelin-sequestered pool); however, the distribution of PFO* binding sites on the plasma membrane was not addressed.…”
mentioning
confidence: 99%